Tonsillitis-Related Arthritis: Advanced Understandings of Tonsillitis and Sterile Inflammatory Arthritis - Shigeto Kobayashi; Issei Kida; Yuuki Makiyama; Yoshinori Taniguchi; Kurisu Tada; Naoto Tamura (Case Reports in Rheumatology)
A 49-year-old man developed acute aseptic arthritis of the nonmigratory and asymmetrical type in his knee, ankle, and bilateral metatarsal joints 13 days after treatment with antibiotics for acute tonsillitis. He was diagnosed with tonsillitis-related arthritis after other rheumatic diseases were ruled out. Treatment with salazosulfapyridine, methotrexate, and methylprednisolone for 3 months did not completely improve. Then, tonsillectomy was undertaken and arthritis rapidly improved. Finegoldia magna (previously Peptostreptococcus magnus) was cultured from the microabscesses of the resected tonsils. After outpatient follow-up, the patient did not experience a relapse of arthritis for more than 2.7 years without any treatment. Poststreptococcal reactive arthritis (PSRA) is well described. However, up to 40% of patients with tonsillitis-related arthritis did not demonstrate evidence of streptococcal infection. It is noted that tonsillectomy is necessary to remove the tonsillar microabscesses and eradicate bacterial infection of the tonsils, especially for patients with a prolonged and/or recurrent course of PSRA and/or tonsillitis-related arthritis.